Implementasi Program E-SAMSAT Wajib Pajak Kendaraan Bermotor Tahunan - Rosa Aida Afifah; Tukiman Tukiman (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2024)
Payment of vehicle tax is an obligation for all Indonesian people who own motorized vehicles. The government as motor vehicle tax collector has innovations in paying motor vehicle tax so that it is able to adapt to the current phenomenon, namely the development of the digital world or the internet. The program resulting from government innovation is called E-SAMSAT. The E-SAMSAT program aims to make it easier for motor vehicle taxpayers to make tax payments without having to visit the SAMSAT office. This research was conducted to determine the implementation of the E- SAMSAT program in East Surabaya. This research uses a qualitative descriptive method with data collection techniques of observation, interviews and document study. Based on the research results, the implementation of the E- SAMSAT program in East Surabaya has been implemented well because the aim of the program is to be implemented, namely the motor vehicle tax payer community. The SAMSAT office also implements training for staff. The community groups for whom the E- SAMSAT program services were implemented received it well.